2017
DOI: 10.1111/jocn.14197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shift work on intensive care nurses’ lives outside work: A cross‐sectional study

Abstract: By identifying modifiable areas which negatively influence life outside work when working shifts, it will be possible subsequently to plan interventions aimed at decreasing the negative effects. Interventions may include nurses having increased influence on their work schedules and education in sleep hygiene and dietary habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 25 publications
8
53
0
1
Order By: Relevance
“…Furthermore, this study has shown that the social effects of night shift work are driven by the nurses' concerns about their inability to maintain social relationships while working night shifts and that this effect is lowered if they receive understanding and support from their family members. This finding is consistent with other studies that have shown that the nurses engaged in night shifts experience social isolation and lower partnership and job satisfaction rates [23,24,25,26]. Another study showed that lack of support from family members also increases the social effects of night shift work among nurses [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, this study has shown that the social effects of night shift work are driven by the nurses' concerns about their inability to maintain social relationships while working night shifts and that this effect is lowered if they receive understanding and support from their family members. This finding is consistent with other studies that have shown that the nurses engaged in night shifts experience social isolation and lower partnership and job satisfaction rates [23,24,25,26]. Another study showed that lack of support from family members also increases the social effects of night shift work among nurses [21].…”
Section: Discussionsupporting
confidence: 91%
“…Ferri et al showed higher rates of psychological symptoms but lower rates of intimate partnership and job satisfaction among night shift nurses compared to day nurses in a study in Northern Italy [22]. In addition, Jensen et al, showed that almost a third of evening and night shift nurses in Denmark reported being socially isolated [23]. Moreover, there is a negative impact of night shift work on social engagement.…”
Section: Introductionmentioning
confidence: 99%
“…The study also measured the association between night work and the dimensions of risk of illness, and it was found that it is approximately three times more likely to present risk of illness for physical cost among night shift workers than those who works during the day. Literature data corroborate the findings of this investigation, identifying that working at night increases the risk of depersonalization (22) , with higher prevalence of mood swings and headaches among night workers (23) .…”
Section: Discussionsupporting
confidence: 85%
“…Beyond this, shift irregularity may cause job dissatisfaction because nurses value work-life balance and a planned personal life [38]. Studies have reported that working rotating shifts can cause social isolation [39]. Still, nurses with counterclockwise rotating schedules (which rotate from night to evening to morning shifts) experience more di culty balancing work and social/family life than those who work clockwise schedules (which rotate from morning to evening to night shifts) [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that working rotating shifts can cause social isolation [39]. Still, nurses with counterclockwise rotating schedules (which rotate from night to evening to morning shifts) experience more di culty balancing work and social/family life than those who work clockwise schedules (which rotate from morning to evening to night shifts) [39,40]. Furthermore, nurses with children experience various challenges when working rotating shifts, including feeling guilty [27,37], unsafe, stressed, and exhausted [26].…”
Section: Discussionmentioning
confidence: 99%